From Waste to Worth: Unlocking the Potential of Liquid Biomethane for a Decarbonized Energy Future - Muchiri, Kang’ethe B; Odoyo, Wilfred O; Kagere, Kabugo E; Wambui, John K (IC-ITECHS, 2024)
Liquid biomethane (LBM), derived from purified biogas, is a low-carbon, renewable energy source that can contribute to energy security and climate change mitigation. LBM produces a transportable, high-density fuel that can replace fossil fuels in a range of industries by turning organic waste into a liquid energy source. This study looks at the properties of liquid biomethane, the processes required to produce and liquefy it, and its use in transportation, industry, and power generation. The report highlights the ways in which LBM advances worldwide decarbonization efforts, reduces greenhouse gas emissions, and aids in waste management. Technical challenges and emerging opportunities are also discussed to chart the path for LBM's adoption in a sustainable energy future.